Direct Comparison of Two New Actigraphs and Polysomnography in Children and Adolescents - Meltzer, Lisa J.; Walsh, Colleen M.; Traylor, Joel; Westin, Anna M. L. (Sleep (New York, N.Y.), 2012)
To evaluate the validity and reliability of 2 new models of commercially available actigraphs compared to polysomnography for children and adolescents. Subjects concurrently wore the Ambulatory Monitoring Inc. Motionlogger Sleep Watch (AMI) and the Phillips Respironics Mini-Mitter Actiwatch-2 (PRMM) while undergoing overnight polysomnography (PSG) in a pediatric sleep laboratory housed in a tertiary care children's hospital. 115 youth (59 girls, 56 boys), ages 3-18 years (mean 8.8 years, SD 4.4 years). Outcome variables were total sleep time (TST), wake after sleep onset (WASO), and sleep efficiency (SE). Epoch-by-epoch comparisons were made between the 2 devices and PSG to determine sensitivity, specificity, and accuracy. Agreement between the 2 devices was determined with t-tests and the Bland-Altman concordance technique. Different algorithms/sensitivities, developmental age groups, and sleep disordered breathing (SDB) status were also examined. For both device brands, sensitivity (0.89-0.97), specificity (0.54-0.77), and accuracy (0.87-0.90) were similar to previous reports. Notably, compared to PSG, both device brands significantly overestimated WASO, while the AMI device also significantly underestimated TST. Inter-device comparison of the 2 brands found poor agreement for TST, WASO, and SE. Agreement with PSG differed depending on the scoring algorithm (AMI) or sensitivity setting (PRMM), as well as across developmental age group and sleep disordered breathing (SDB) status. Similar to previous reports, both new actigraph brands were found to have good sensitivity (to detect sleep), but poorer specificity (to detect wake). Study results also suggest that researchers should adjust the scoring algorithm/sensitivity depending on a study's design (e.g., young children vs. adolescents, healthy children vs. youth with SDB). Further, inter-device reliability was poor, suggesting the need for caution when comparing results across studies that use different brands of actigraphic devices.